Geothermal Reservoir Characterization for Steam Field Management in Kamojang Geothermal Field-West Java - Z. Abidin; R. Prasetio; Prayoto Prayoto (PPIKSN-BATAN, 2009)
Kamojang is the first geothermal field in Indonesia with a vapor dominated system reservoir. Kamojang has been exploited for over 20 years producing about 1100 tons/hour of steam which is equivalent to 140 Mwe electricity energy. This research is aimed to study the reservoir character after 20 years of exploitation and to investigate the effect of reinjection as a artificial recharge for steam input in the future and also the nature of secondary processes in the reservoir using isotope geochemistry tools. The research is conducted by natural isotopes (18O, 2H and 3H) analysis of many sources of water (meteoric, cold spring, fumaroles and shallow groundwater) in the surrounding of Kamojang field and also fluid reservoir to establish fluid reservoir origins and isotopic composition. Gas analysis and isotopes monitoring on the 25 production wells have been conducted every 2-3 years intervals for more than 10 years to investigate the effect of exploitation to the reservoir performance. Tritium radiotracer test with 370 GBq (10 Ci) activity was conducted at the KMJ 15 reinjection well to determine qualitatively and quantitatively the flow of reinjection water to its surrounding producing well (KMJ 11, 14, 17, 18, 26, 17 and 30). Data interpretation and evaluation to determine reinjection water mass recovery and cooling prediction modeling were conducted using ICEBOX program package (TRINV and TRCOOL). Interpretation and evaluation of data concluded that reservoir fluid of Kamojang geothermal field was originated from meteoric water which infiltrated through fault structures at elevation of 1350 m –1650 m above sea level. There is no evidence that the fluid was originated from magmatic water. Reservoir fluid moved both laterally and vertically (deep fluid) with lateral fluid movement from west to the east. The isotope data analysis indicated there is water entry in west-northwest reservoir boundary. Water entry gradually moved from northwest to the southeast (through wells of KMJ 42, 40, 27, 26 and 28). Exploitation effect to ten of the observation wells shows a decrease in w/r ratio and liquid saturation from 35 % in the beginning to about 20,5 % on the average after 20 years of operation. Evaluation with TRINV and TRCOOL program shows that 13,5 % of water reinjected into KMJ 15 reinjection well was recovered in the surrounding production wells. The program model of the reservoir temperature cooling shows that water reinjection with flow rate of 10 kg/sec is very save. After 20 years of reinjection activity, the model predicts a production wells will be cooling of about 6.8oC.Received: 15 January 2009; Revised: 1 May 2009; Accepted: 5 May 2009